PENGARUH PELATIHAN, KOMPENSASI DAN PROMOSI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARAYAWAN - Sugiyarto, Sugiyarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to determine the effect of training, compensation, promotion on work motivation and its impact on employee performance. The research took 100 respondents / employees who lived in the South Tangerang City area, using descriptive quantitative methods with path analysis. The research results show that training does not affect work motivation as evidenced by the sig value of this variable being greater than 0.05. Meanwhile, the results of data processing on promotion and compensation have quite a significant influence based on the analysis results where each variable has a sig value of 0.00 and 0.009 or smaller than 0.05